CORRELATION BETWEEN SALIVARY CONSTITUENTS OF FATHER AND CHILD - DESHPANDE, RAHUL R.; BENDGUDE, VIKAS; S. METHA, BHAVANA; JADHAV, MEGHA; MUTHA, MAYURI; CHHABRA, RAJDEEP SINGH; TUSHAR.V.GADKARI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: The objective of the study was to find out the correlation between the salivary amino acids and electrolytes in saliva of the father and the child. Method: Saliva was collected from nine father and child pairs by method of Passive Drooling. Qualitative amino acids analysis and electrolyte analysis of the salivary samples was done by LCMS (shimadzu 2010, single quadrupole detector with electrospray ionization).Â Results: The three amino acids with highest concentration found in fathers' saliva were arginine, histidine and tryptophan while in children glycine, phenyl alanine and tryptophan were found. The only common amino acid in both groups was tryptophan. Sodium, potassium and calcium were the three ions with maximum concentration in both fathers' and children's saliva. Sodium and calcium levels were found to be comparable but the potassium levels were significantly different. Conclusion: A definitive correlation could not be established between a father's and the child's saliva. Further investigations with large sample size and including more parameters will help us establish whether or not there is any correlation between the salivary constituents of a father and child. Â KEY WORDS: saliva, salivary constituents, free amino acids, cations, correlation, father, child